KEWARISAN ANAK ANGKAT YANG BERKEDUDUKAN SEBAGAI ASHÂBUL FURÛDH (Analisis Terhadap Putusan Pengadilan Agama No. 287/Pdt.G/2006/PA.Pdg.) - Alfiander, Dodon (JURIS (Jurnal Ilmiah Syariah), 2018)
The Case No. 287/ Pdt. G/ 2006/PA. Pdg. is a lawsuit Wasiat Wajibah submitted to the Religious Court of Padang. The Religious Court of Padang sets the plaintiff on this case as an adopted child who is entitled to obtain a mandatory will from his foster mother's estate. Where as between the plaintiff and his adoptive mother has a very close kinship relationship. The plaintiff is the real child of his adoptive brother's brother, while at that moment the plaintiff's adoptive mother was the heir of Kalâlah. The Law of Inheritance of Islam recognized the right of inheritance to the sister’s child. Sister’s son's inheritance is not clearly contained in the Qur'an and the hadith of the Prophet Muhammad pbuh. However, sister’s child's inheritance rights are basically through the extension of the understanding of other whose rights are described in the Qur'an, because if he or she has no sister and brother, the position can be replaced by the child. Sister’s child will not get the right as long as his father who connects him to the heir is alive. This can be understood as the concept of "Expanding Brotherhood Meanings". Thus, the decision of the Religious Court of Padang on the Wasiat Wajibah which sets the plaintiff to obtain the right to the property of his adoptive mother through Wasiat Wajibah is not appropriate. This is because the plaintiff has a very close kinship with his adoptive mother. Therefore, the plaintiff is more aptly part of the heritage of his adoptive mother through his right as an heir (ashâbul furûdh), not as a mandatory will. This is because the plaintiff replaces the position of his biological father as the heir because he has died earlier than his adoptive mother. The Plaintiff is entitled to receive a share of furûdh against the inheritance of his adopted mother. The furûdh portion obtained is based on the letter of al-Nisâ verse 176.